Investigating the effect of Sclareol on IRE-1 and PERK genes the pathway of reticulandaplasmic system stress in gastric cancer cells MKN-45 - Elmira Aboutalebi; Ebrahim Sakhinia; Vand Beilanokhi; Homayoun Dolatkhah (Journal of Research in Applied and Basic Medical Sciences, 2020)
Background & Aims:  Despite the decline in the prevalence of gastric cancer in recent years, it remains the fourth leading cause of death from cancer in the world. Common cancer treatments may reduce the size of the tumor, but it is transient and does not have a positive effect on the patient's survival and there is a possibility of recurrence of the disease. Strong induction of reticulom endoplasmic has been shown to increase the susceptibility to anti-cancer therapy. Regarding the importance of medicinal herbs in recent years and its low side effects after administration, compared with synthetic drugs, this study investigated the effects of salvia Sclareol purification from sage on the induction of reticulum endoplasmic system stress. Materials and Methods: The MKN-45 cell line from the Pasteur Institute of Iran was purchased and cultured in a complete culture medium of RPMI-1640 with cetacean embryos. Cells cultured with 0, 20, 40, 60, 80 and 100 μm concentrations of Sclareol treatment for 5 hours. The rate of expression of IRE-1 and PERK genes by quantitative real time -PCR and the level of proteins IRE-1 and PERK by western blotting method was investigated. Results: The rate of expression of IRE-1 in doses of 20, 40 and 60 μM Sclareol was significantly increased while decreasing in doses of 80 and 100 μM (p <0.0001). Also, the expression of PERK gene expression at doses of 20, 40 and 60 μM Sclareol was significantly increased, but no increase was observed in doses of 80 and 100 μM (p <0.0001). Also, the levels of IRE-1 and PERK proteins in doses of 20, 40 and 60 micromoles of Sclareol showed a high increase in doses of 80 and 100 μM. Conclusion: From the results of this study, it seems that doses between 20 and 60 μmol of can be Sclareol helpful in increasing the amount of reticuloendoplasmic stress, but doses higher than 60 milimoles do not have like this effect.